Risk of Acute Ischemic Stroke in Covid-19 Patients - Saleha Islam, Ahmed Ejaz, Ahmed Ammad, Muhammad Abdullah Islam, Asma Kanwal, Rabia Islam, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Research on large groups of COVID-19 patients in terms of risk factors for acute ischemic stroke, events that occur in the hospital, and outcome is lacking. Acute ischemic stroke frequency was determined in both COVID-19-positive and non-positive individuals. Those results were then compared to those of people who had an acute ischemic stroke but did not have COVID-19. Methods: Based on the Cerner COVID-19 collection of de-identified data from 5 healthcare facilities, we were able to do our analysis in the Institute of Public Health Sciences Lahore. No patients were left out of the experiment because they had a COVID-19-related discharge diagnosis or a confirmed COVID-19 infection. Results: Out of the 8163 people who took part in the COVID-19 study, 103 (1,3%) had an acute ischemic stroke. Risk factors for cardiovascular disease like high blood pressure and diabetes were found to be more common in people who had had an acute ischemic stroke than in the general population. After taking into account possible confounding factors, the risk of an acute ischemic stroke was found to be higher (relative risk: 2.0; 95 percent confidence interval (CI): 1.0–2.4; P0.0001). Ischemic strokes happened to most of the people who didn't get COVID-19 in the first three months. After taking into account other important factors, COVID-19 was linked to a 1.2 (95 percent CI: 1.0–1.3) relative risk of death or discharge to a place other than home for all ischemic stroke patients (P = 0.03). Conclusions: People in the COVID-19 cohort had a very low rate of acute ischemic stroke if they didn't have any other heart disease risks. In the COVID-19 study, people who had an acute ischemic stroke were twice as likely to have to go back to the hospital or die.